MAKNA SIMBOLIK RITUAL SULUK SEBAGAI MEDIA TRANSFORMASI KESADARAN SPIRITUAL MASYARAKAT ISLAM - Iswadi Iswadi; Helmi Abu Bakar (Jurnal Komunikasi dan Media, 2025)
Suluk rituals in the Sufi tradition constitute spiritual practices rich in religious symbols that function as a medium for shaping and transforming the spiritual consciousness of Muslim communities. This article aims to analyze the symbolic meanings embedded in suluk rituals and their role in transforming both spiritual and social consciousness among participants. This study employs a library research methodology with a qualitative-descriptive approach, examining classical Sufi texts and relevant scholarly literature. The findings indicate that the main symbols in suluk—such as the mursyid, the kelambu (veil), and the tasbih (prayer beads)—serve educational, psychospiritual, and social functions. The mursyid acts as a spiritual guide and psychosocial regulator, the kelambu represents an awareness of death that is reflective and therapeutic in nature, while the tasbih symbolizes disciplined remembrance (dhikr) with implications for mental health and moral character formation. Overall, suluk rituals form an integrative symbolic system that fosters individual spiritual awareness as well as collective social consciousness within Muslim society.